3-D lithofacies Model of Mishrif Formation in Nasiriyah oil field Southwestern Iraq - Hlelai, Mahmoud; Khorshid, Salman (Iraqi Journal of Science, 2025)
Petrophysical data interpretation study has been done for ThiQar – Nasiriya oil field at the southwestern part of Iraq in order to build the 3-D lithofacies model of the Mishrif reservoir which currently is the main unit of bearing the oil in subsurface area covered about (447) km2. This study is achieved by using CMG, Petrel, Techlog, and other approval software. The study depended on the direct and indirect well logs data analysis supported with coring analysis, and drilling geological reports. The lithofacies of Mishrif Formation units detected form direct logs responses on behavior of SP, Resistivity, and GR logs, and from indirect analysis on behavior of (ØN-ρb) crossplots where the values of the both parameters projected in the limestone zone, some in dolomite and little in sandstone zone. The same case is for most of the wells with little difference in wells NS-12, 13, and 14 that properly have behavior of sandstone. In addition, the result is supported by coring description during the drilling. The results of the analysis integrated and distributed by sequential indicator simulation method as maps and 3D model. The lithofacies model of Mishrif Formation units in this study helped us to estimate the geological environmental deposition facies for each unit which was graduated from back reef in west and NW to the reef in the middle, fore , and slope in SE of the field.